Deformabilidade de subleitos de trechos monitorados da BR 116/RS considerando variações de umidade em laboratório e campo - Pascoal, Paula Taiane (2024)
Considering the deformability of the layers that make up the pavement is essential for proper design and to avoid pathological manifestations such as fatigue cracking and rutting. In the case of subgrade soils, which are subject to seasonality, attention must be paid to variations in behavior in the face of changes during the useful life and demands of the pavement. The aim of this thesis was to evaluate the soils used in the subgrade of the BR 116/RS, both in the laboratory and in the field. To this end, an experimental program was developed to characterize the elastic and plastic behavior of the materials under different humidity conditions, associated with the monitoring of sections with emphasis on rutting and subgrade humidity measurements. To simulate the moisture variation ranges that the materials could be subjected to in the field, drying and wetting paths of ±2% and ±4% were imposed on the post-compaction samples. Thus, it was possible to identify different behaviors in terms of resilient modulus and permanent deformation, verifying gains in stiffness with drying and the susceptibility of each material to lose stiffness and increase permanent deformation with access to post-compaction moisture. Based on the elastic and plastic parameters of the soil conditions evaluated, as well as the other components of the pavement, it was possible to predict the behavior of the monitored sections using the MeDiNa software, which was compared with the actual performance of the different segments. It was found that on the sections where the subgrade showed greater variations in humidity, the forecast and the measured mechanical performance were different, while on the sections where humidity tended to balance, the forecast is consistent with the performance to date. In addition, a soil characterization methodology was developed using rheometric tests to understand the stiffness of compacted soils under different post-compaction conditions. This methodology proved promising for identifying the stiffness at small deformations, making it possible to use it for prior characterization or for selecting suitable materials for use in subgrade.